Development Village Tour Based on Technopreneurship in Kendal Regency - Danang Dwi Saputro; Margareta Rahayuningsih; Margunani Margunani; Bunyamin Bunyamin; Widi Widayat; Dadan Budiansyah (Jurnal Abdimas, 2024)
Pokdarwis Gunungsari Pucuke Kendal (Mitra) Ngesrepbalong Village, Limbangan District, Kendal Regency was formed in 2016 through a village deliberation forum and in 2022, Ngesrepbalong Village was officially designated as a tourist village based on the Decree Kendal Regent Number 556/343/2021. Gunungsari Pucuke Kendal Pokdarwis is led by Wahyudi as chairman with a board of administrators who manage several mainstay tourist attractions. The local potential of Ngesrepbalong Village consists of natural tourist attractions, biodiversity, cultural attractions and local processed products. The problems experienced by partners are (1) The problematic aspects are related to branding and promotion of tourism potential that has not been optimal. Not yet there is a design destination branding as identity For introduce tourist Village It's so long. For example, improving tourism infrastructure to support branding and the identity of tourist destinations, (2) Conditions in the field show limited human resources to promote tourism through social media, (3) the absence of technology/tools that help sort coffee by size, so that sorting is done manually. The output targets of the solutions offered include (1) Availability of digital tourism packages presented on websites and social media, (2) The availability of embossed letter branding for regional identity, (3) Coffee grader machines are available, (4) 200 environmentally friendly coffee packages are available from paper craft, and (5) As many as 15 Pokdarwis members and UMKM post-harvest coffee processing have increased their capacity and knowledge in technology-based business management. Plan activity Which proposed (1) Socialization And coordination beginning, (2) Training administration and planning professional BUMDes business, (3) Branding training through destination branding design (4) Training technopreneurship-based business management , (5) Facilitation of TTG grader machines and environmentally friendly packaging (5) Mentoring, and (6) Evaluation. The outputs of community service are (1) Accredited national journals, (2) Print/electronic media publications, (3) Video documentation, and (4) increasing community knowledge and skills.